Analisis Perkembangan Pemahaman Part of Speech pada Mahasiswa Tingkat Pertama Teknik Komputer - Saputri, Yun; Sulfirani, Siti; Jumria; Sulham, Baso (INTENS Jurnal Inovasi Sains Teknologi dan Bisnis, 2025)
Understanding parts of speech is a fundamental component in learning English, particularly for first-year university students who are being introduced to basic grammatical structures. This study aims to analyze the development of parts of speech comprehension among first-year students in the Computer Engineering Program at the Institut Teknologi dan Sains Muhammadiyah Kolaka Utara. A descriptive method was employed, utilizing both qualitative and quantitative approaches. Data were collected from student assignments and their scores in the Mid-Semester Examination (UTS) and Final Semester Examination (UAS). The results indicate that most students showed significant improvement, with over 80% achieving grades of A or B. However, a number of students demonstrated stagnation or a decline in performance, which may be attributed to academic factors such as the complexity of UAS material and non-academic factors including motivation and learning preparedness. This study highlights the need for more interactive and contextual teaching methods, as well as additional guidance for students facing difficulties. With the right instructional strategies, students are expected to master parts of speech comprehensively, equipping them to meet both academic and professional challenges in the future.